Experiential Learning Sebagai Teknik Bimbingan Klasikal Untuk Meningkatkan Pemahaman Karier Siswa - Fuad, Anik Hermawati; Salim, Moch Nur; Hariastuti, Retno Tri (Universitas Nusantara PGRI Kediri, 2022)
Career understanding is considered very important to prepare professional planning according to talents and interests to determine future job choices. This study aimed to measure the effectiveness of the classical experiential learning method in improving students' career understanding. The research method uses a quantitative approach with an equivalent time series design research design. The study results show that the experiential learning method of classical guidance services is proven effective in increasing students' career understanding. After having a good understanding of careers, students are expected to be able to develop a career plan and choice and be able to realize it in real action.